Migraine Types and Triggering Factors in Children - NEJAD BIGLARI, Habibe; KARIMZADEH, Parvaneh; MOHAMMADI KORDKHEYLI, Marzieh; HASHEMI, Seyedeh Masumeh (Iranian Journal of Child Neurology, 2012)
How to Cite this Article: Nejad Biglari H, Karimzadeh P, Mohammadi Kord-kheyli M, Hashemi SM. Migraine Types and Triggering Factors in Children. Iran J Child Neurol 2012;6(2):33-38. Objective Migraine is a common problem in children and the mean prevalence of migraine in Europe among 170,000 adults was 14.7% (8% in men and 17.6% in women) and in children and youth (36,000 participants), the prevalences were (9.2% for all, 5.2% in boys and 9.1% in girls) and the lifetime prevalences were (16, 11 and 20%, respectively). To determine the epidemiology of migraine and evaluate migraine triggering factors in children. Materials & Methods Two-hundred twenty-eight children with a maximum age of 12 years who fulfilled the ICHD-II criteria for pediatric migraine were enrolled into the study. Results This study shows that migraine is slightly more common in boys and its peak incidence is between ages 8 and 12 and most patients have three to five headache attacks per month. The pain has a tightening, stabbing or vague quality in about 70% of children with migraine and bilateral headache is slightly more common. The common triggering factors in children migraine were stress, noise, sleeplessness, hunger and light and the common relieving factors were sleep, analgesics, silence, darkness and eating. Conclusion Migraine is a common problem in children with an equal incidence in boys and girls before adolescence and more common in girls after adolescence. References Powers SW, Andrasik F. Biobehavioral treatment, disability, and psychological effects of pediatric headache. Pediatr Ann 2005;34(6):461-5. Rosenblum RK, Fisher PG. A guide to children with acute and chronic headaches. J Pediatr Health Care 2001;15(5):229-35. Fallahzadeh H, Alihaydari M. Prevalence of migraine and tension-type headache among school children in Yazd, Iran. J Pediatr Neurosci 2011;6(2):106-9. Ayatollahi SM, Khosravi A. Prevalence of migraine and tension-type headache in primaryschool children in Shiraz. East Mediterr Health J 2006;12(6):809-17. Stovner LJ, Andree C. Prevalence of headache in Europe: a review for the Eurolight project. J Headache Pain 2010;11(4):289-99. Bille B. A 40-year follow-up of school children with migraine. Cephalalgia 1997;17(4):488-91; discussion 487. Bille B. Migraine and tension-type headache in children and adolescents. Cephalalgia 1996;16(2):78. Bille B. Migraine in childhood and its prognosis. Cephalalgia 1981;1(2):71-5. Lewis DW, Ashwal S, Dahl G, Dorbad D, Hirtz D, Prensky A, et al. Practice parameter: evaluation of children and adolescents with recurrent headaches: report of the Quality Standards Subcommittee of the American Academy of Neurology and the Practice Committee of the Child Neurology Society. Neurology 2002;59(4):490-8. Shah UH, Kalra V. Pediatric migraine. Int J Pediatr 2009;2009:424192. Fukui PT, Gonçalves TR, Strabelli CG, Lucchino NM, Matos FC, Santos JP, et al. Trigger factors in migraine patients. Arq Neuropsiquiatr 2008;66(3A):494-9. Neut D, Fily A, Cuvellier JC, Vallée L. The prevalence of triggers in paediatric migraine: a questionnaire study in 102 children and adolescents. J Headache Pain 2012;13(1):61-5. Lewis DW, Diamond S, Scott D, Jones V. Prophylactic treatment of pediatric migraine. Headache 2004;44(3):230-7. Barabas G, Matthews WS, Ferrari M. Childhood migraine and motion sickness. Pediatrics 1983;72(2):188-90. Holguin J, Fenichel G. Migraine. J Pediatr 1967;70(2):290-7. The International Classification of Headache Disorders: 2nd edition. Cephalalgia 2004;24 (Suppl 1):9-160.